1992
DOI: 10.1002/hlca.19920750205
|View full text |Cite
|
Sign up to set email alerts
|

Synthese und Reaktionsverhalten 2′‐substituierter Isoflavone

Abstract: The protected chalcones 6 8 prepared from acetophenone and henzaldehydes rearranged to the dimethoxypropanone derivatives 9-11 in the presence of trimethyl orthoformate by T1(NO3),.3 H20. These compounds could he cyclized to the isoflavones 12-14 in high yields (Scheme 2). The conversion of these isoflavones to the corresponding isoflavanes (model compounds of the phytoalexin glabridin; see Scheme I ) was the main goal of this work. Hydrogenation of 13 and 14 gave the isoflavanes 15 and 16, respectively, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The reaction led to the monoether in position 4, and the diethers in positions 2 and 4. To obtain products with lower molecular mass and fewer NMR signals, the introduction of MOM protecting groups (1 3 2; Scheme 2) seemed to be advantageous [11]. The acid-catalyzed deprotection turned out to occur under milder reaction conditions compared to the MEM ethers.…”
mentioning
confidence: 98%
“…The reaction led to the monoether in position 4, and the diethers in positions 2 and 4. To obtain products with lower molecular mass and fewer NMR signals, the introduction of MOM protecting groups (1 3 2; Scheme 2) seemed to be advantageous [11]. The acid-catalyzed deprotection turned out to occur under milder reaction conditions compared to the MEM ethers.…”
mentioning
confidence: 98%
“…The resonance contributor 10 will encourage this mode of attack. DIBAH, normally a preferential 1,2-reducer, reacts with methoxy-, benzyloxy-, MOMO- and MEMO-substituted isoflavones to give the isoflavanones in 40–93% yield [ 16 , 21 - 23 ] (Table 1 ). Our own work has shown that even unprotected hydroxy-substituted isoflavones are reduced by a large excess of DIBAH in 50–70% yield (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is no significant difference between the K- and L-Selectride ® . In the literature, there is an isolated report of the reduction of a MOM substituted isoflavone by L-Selectride ® in 40% yield (Table 2 ) [ 16 ]. Methoxy substituted isoflavones have also been reduced by sodium hydrogen telluride to give isoflavan-4-ones in 61–71% yields [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations